Student entrepreneurship in universities: The state-of-the-art - Federico Schimperna; Fabio Nappo; Bruno Marsigalia (Administrative Sciences, 2022)
The purpose of this paper is to understand how universities develop and support student entrepreneurship. We did a preliminary Systematic Literature Review (SRL) on scientific articles regarding student entrepreneurship published during the last twenty years. Our findings emphasize three main research areas, emerging from a cluster analysis: (i) student entrepreneurship and entrepreneurial intention; (ii) university support for entrepreneurship; (iii) entrepreneurship education and learning. Particularly, our study points out that the new paradigm of the entrepreneurial university overcame the classical university model through the introduction of many innovations to foster student entrepreneurship. This paper provides an SLR on university role in fostering student entrepreneurship and it is useful for the academic and professional community. Additionally, it is original because it highlights the future directions of entrepreneurship and the main innovations adopted by universities to help students in the development of entrepreneurial initiatives.
Keywords: 350; active entrepreneurship; nascent entrepreneurship; student entrepreneurship; student venture creation; university